Crustal thickness of the Jiaodong Peninsula in the Mesozoic: Implications for the destruction of the North China Craton - Dong, Leilei; Bai, Xin; Song, Mingchun; Wang, Runsheng (Frontiers in Earth Science, 2023)
The North China Craton underwent extensive and widespread crustal reworking (or decratonization) during the Mesozoic. However, how the decratonization operated is not well understood. Zircon compositions are widely used by the scientific community to reconstruct crustal thicknesses. In this study, we sampled 13 magmatic rocks in the Jiaodong Peninsula and used zircon Eu/Eu* to constrain the crustal thickness of the Jiaodong area and reveal decratonization processes in the Mesozoic time. The reconstructed crustal thickness using zircon Eu/Eu* is approximately 70 km in the Jurassic, and this value is 89 km at around 130 Ma, after which the crustal thickness drops to 30–40 km at ca. 110 Ma. These results are generally compatible with or slightly higher than the calculation results using a whole-rock La/Yb proxy for the Jurassic and ∼130 Ma rocks. Crustal thickness estimated using a whole-rock La/Yb proxy for the ∼110 Ma rocks is thicker than 70 km, which is not consistent with the geological facts and the result given by zircon proxy. The whole-rock proxy failed in estimating crustal thickness because of amphibole fractionation for the ∼110 Ma rocks. The crustal thickening from Jurassic to ∼130 Ma was probably related to the westward subduction of the Paleo-Pacific slab. The thinning of the crust from 130 to 110 Ma is not a rapid process but occurs more slowly than expected, which might be explained by the chemical erosion process rather than a mechanical delamination model. The chemical erosion was most likely induced by a rollback of the subducting slab and an upwelling of the asthenosphere.